Macroinvertebrates in Disturbed and Undisturbed Sites in Asap, Belaga - Goh, Emmy Ling Ling (Universiti Malaysia Sarawak, UNIMAS, 2010)
Species diversity of macroinvertebrate among three different types of land uses, namely Malaysian Palm Oil Board area to be developed (BDA), a 20-year logged over forest streams (LOF) and 7-year oil palm plantation (7OP) was compared. The categories of water quality of the streams were evaluated using macroinvertebrates as the biological indicators with Average Score per Taxon (ASPT) and taxa richness of Ephemeroptera, Plecoptera and Trichoptera (EPT) as the biological indices. Environmental variables such as pH, temperature, dissolved oxygen, water current, depth, and wetted width were significantly associated with the abundance of macroinvertebrates. A total of 4,776 individuals comprising 18 orders, 65 families, 76 genera and 95 species of macroinvertebrates were recorded from the three land uses. LOF has the highest taxa richness during wet season with 52 species, followed by BDA with 45 species also in wet season and 7OP with 29 species during dry season. Stream in BDA has the lowest number of individuals with 292 individuals. Environmental and species variables were correlated with seasons and type of land uses where seasons give much more influence than land uses due to unclear categorization of disturbed and undisturbed streams. The biological indicator generally showed BDA, LOF and 7OP streams were moderately polluted. Consecutively, Canonical Correspondence Analysis, Multi-response permutation procedure and indicator species analysis were conducted and showed that the community structure of macroinvertebrate was significantly different between BDA and LOF sites. Functional feeding groups revealed land uses have influenced the food resources for the macroinvertebrate subsequently affect the functional groups.